Influence of underlying condition and performance of sepsis bundle in very old patients with sepsis: a nationwide cohort study - Duk Ki Kim; Soyun Kim; Da Hyun Kang; Hyekyeong Ju; Dong Kyu Oh; Su Yeon Lee; Mi Hyeon Park; Chae-Man Lim; YunKyong Hyon; Song I Lee; the Korean sepsis Alliance (KSA) investigators (Annals of Intensive Care)
Abstract Background Sepsis is a life-threatening condition that affects individuals of all ages; however, it presents unique challenges in very old patients due to their complex medical histories and potentially compromised immune systems. This study aimed to investigate the influence of underlying conditions and the performance of sepsis bundle protocols in very old patients with sepsis. Methods We conducted a nationwide cohort study of adult patients with sepsis prospectively collected from the Korean Sepsis Alliance Database. Underlying conditions, prognosis, and their association with sepsis bundle compliance in patients with sepsis aged ≥ 80 years were analyzed. Results Among the 11,981 patients with sepsis, 3,733 (31.2%) were very old patients aged ≥ 80 years. In-hospital survivors (69.8%) were younger, less likely male, with higher BMI, lower Charlson Comorbidity Index, lower Clinical Frailty Scale, and lower Sequential Organ Failure Assessment (SOFA) scores. The in-hospital survivor group had lower lactate measurement but higher fluid therapy and vasopressor usage within the 1-h bundle. Similar trends were seen in the 3-h and 6-h bundles. Furthermore, in-hospital survivors were more likely to receive appropriate empiric antibiotics within 24 h. In-hospital mortality was associated with age, Clinical Frailty Scale, SOFA score, comorbidities, Life sustaining treatment issue, interventions in the ICU and vasopressor use in the 1-h sepsis bundle. Conclusions Addressing underlying conditions and enhancing sepsis bundle adherence is crucial for better outcomes in very old patients with sepsis. Personalized approaches and increased awareness are essential. Further research should explore interventions to optimize sepsis care in this population.